Differential gene expression analysis of dasatinib-induced colitis in a patient with chronic myeloid leukemia followed for 3 years: a case report - Oshima, Naoki; Mishima, Yoshiyuki; Shibagaki, Kotaro; Kawashima, Kousaku; Ishimura, Norihisa; Ikejiri, Fumiyoshi; Onishi, Chie; Okada, Takahiro; Inoue, Masaya; Moriyama, Ichiro; Suzumiya, Junji; Kinoshita, Yoshikazu; et al. (BMC gastroenterology, 2021)
Background Dasatinib is a second-generation tyrosine kinase inhibitor (TKI) developed for treatment of patients with chronic myeloid leukemia (CML). The drug has been shown to act as a potent multikinase inhibitor by blocking not only the BCR-ABL1 gene sequence but also the SRC kinase family, though unexpected adverse events such as pleural effusion have recently been reported in patients undergoing treatment with dasatinib. Hemorrhagic colitis is a unique gastrointestinal adverse events associated with dasatinib and its pathogenesis remains poorly understood. Case presentation We report here a case of dasatinib-induced asymptomatic colitis in a patient with CML, who showed no exacerbation in careful observations and maintained deep molecular response (DMR) during a 3-year period. In addition, we performed transcriptome analysis of inflamed colonic mucosa specimens to clarify the possible mechanism of colitis that develops in association with dasatinib administration. Our results demonstrated that differential gene expression, especially lymphocyte-associated genes and chemokines, is substantially involved in inflammation of colonic mucosa in affected patients. Conclusion Dasatinib induces immune-mediated colitis following lymphocyte infiltration.